Propyl inulin nanoprebiotics as a synbiotic partner of Lactiplantibacillus plantarum for Inhibiting pathogenic infection in a mouse model - Xueyi Jing; Weiyue Li; Yang Gao; Xin Qiao; Yufei Cheng; Wenjuan Zhang; Lei Pu; Hua Yang; Jianbin Zhang; Liang Hong (Carbohydrate Polymer Technologies and Applications)
Listeria monocytogenes (LM) can proliferate significantly under refrigeration conditions, impacting food storage and safety for humans. This study investigated the effects of different forms of inulin on the antibacterial properties of lactic acid bacteria. Initially, propionylated inulin (IPr) and propyl-inulin nanoparticles (PIN) were synthesized and characterized. Characterization revealed that IPr had an irregular shape, while PIN exhibited a regular spherical structure, with a particle size of 949.7 and 434.4 nm, respectively. The zeta potential of PIN was measured at -51.16 mV. Subsequently, the effects of IPr and PIN on Lactiplantibacillus plantarum (LP) were studied, demonstrating that neither compound negatively affected LP's growth, but both significantly enhanced its antimicrobial activity. Animal studies indicated that LP and PIN had a considerable in vivo antimicrobial impact. They effectively repaired intestinal barrier damage caused by pathogens, alleviated liver injury, regulated immune responses, and restored gut microbiota composition. This study highlights the potent antimicrobial properties of enhanced nanoprebiotics and LP-based synbiotics, which inhibit the growth of psychrotrophic bacteria and promote animal gut health. The study innovatively develops nanoprebiotic-enhanced synbiotics, effectively combating infections, restoring gut health, and offering novel insights for creating additives to improve livestock product quality and shelf life.